Production and mechanical properties of Ti–5Al–2.5Fe–xCu alloys for biomedical applications. (30th January 2018) - Yamanoglu, Ridvan; Efendi, Erdinc; Kolayli, Fetiye; Uzuner, Huseyin; Daoud, Ismail
Abstract: In this study, the mechanical, antibacterial properties and cell toxicity response of Ti–5Al2.5Fe alloy with different copper contents were investigated. The alloys were prepared by high-energy ball milling using elemental Ti, Al, Fe, and Cu powders and consolidated by a uniaxial vacuum hot press. Staphylococcus aureus strain ATCC 29213 and Escherichia coli strain ATCC 25922 were used to determine the antibacterial properties of the sintered alloys. The in vitro cytotoxicity of the samples was evaluated with HeLa (ATTC, CCL-2) cells using thiazolyl blue tetrazolium bromide. The mechanical behavior of the samples was determined as a function of hardness and bending tests and analyzed by scanning electron microscopy, energy dispersive x-ray spectroscopy, optical microscopy and x-ray diffraction (XRD). The results showed that the Cu content significantly improved the antibacterial properties. Cu addition prevented the formation of E. coli and S. aureus colonies on the surface of the samples. All samples exhibited very good cell biocompatibility. The alloys with different copper contents showed different mechanical properties, and the results were correlated by microstructural and XRD analyses in detail. Our results showed that Cu has a great effect on the Ti5Al2.5Fe alloy and the alloy is suitable for biomedical applications with enhanced antibacterial activity.